2018
DOI: 10.15171/jlms.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on Discrimination of Neo-plastic and Non-Neoplastic Gastric Tissues Using Spark Discharge Assisted Laser Induced Breakdown Spectroscopy

Abstract: Introduction: The present work is a novel in vitro study that evaluated the possibility of diagnosing neoplastic from nonneoplastic gastric tissues using spark discharge assisted laser induced breakdown spectroscopy (SD-LIBS) method. Methods: In these experiments, the low energy laser pulses ablated a tiny amount of tissue surface leading to plasma formation. Then, a spark discharge was applied to plasma in order to intensify the plasma radiation. Light emission from plasma was recorded as spectra which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The role of calcium in development of cancers has been discussed in prostate, breast, lung, gastric cancer tissues, and many other organ transformations. 33–41 Most results showed that the concentration of calcium in the malignant tissues was noticeably higher than that of the healthy ones, which is consistent with the results of this work. For PTC, the cancer cells in the nodules grow rapidly, and the proliferation of blood vessels and fibrous tissues in the tumor may lead to the deposition of calcium salts, and even microcalcification clusters.…”
Section: Resultssupporting
confidence: 90%
“…The role of calcium in development of cancers has been discussed in prostate, breast, lung, gastric cancer tissues, and many other organ transformations. 33–41 Most results showed that the concentration of calcium in the malignant tissues was noticeably higher than that of the healthy ones, which is consistent with the results of this work. For PTC, the cancer cells in the nodules grow rapidly, and the proliferation of blood vessels and fibrous tissues in the tumor may lead to the deposition of calcium salts, and even microcalcification clusters.…”
Section: Resultssupporting
confidence: 90%
“…However, many of these methods have not been tested in combination with an ablating laser; studies have focused on tissue differentiation only. In addition to the work carried out in the area of tissue-specific surgery, several studies have used similar approaches for detecting cancer borders during surgery [45][46][47][48][49][50][51]. Each method has its own advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 covers all studies, to the best of our knowledge, related to tissue-specific surgeries. However, the table does not cover works that have used a similar feedback mechanism for detecting cancer margins [45][46][47][48][49][50][51] in the tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Skin cancer is one of the most frequently diagnosed types of cancer worldwide. For the identification and diagnosis of melanoma skin cancer analytical methods such as synchrotron radiation microanalysis (SXRF) [1][2][3], or transmission electron microscopy combined with energy dispersive X-ray analysis (TEM-EDX) [4,5], laser ablation inductively coupled plasma spectrometry, mass spectrometry (LA-ICP-MS) [5][6][7][8], and Raman Spectroscopy are already used [9]. In terms of LIBS sensitivity and spatial resolution with other techniques such as LA-ICP-MS, TEM, Nano-SIM (nanosecondary ion mass spectrometry), EPMA (electron probe micro-analysis), TEM, and SEM (scanning electron microscope), as indicated in [1], which illustrated that LIBS achieves micrometer scale resolution with part-per-million range sensitivities.…”
Section: Introductionmentioning
confidence: 99%
“…e acquisition rate can be very high in LIBS since it is constrained only by the speed of the detector and the frequency rate of the laser. A pace of acquisition up to kilohertz has already been seen [9]. Although these analytical approaches showed high performance in terms of spatial resolution and sensitivity, their relatively slow analysis and the complexity of the required equipment make their use rather restrictive and difficult for routine medical diagnosis.…”
Section: Introductionmentioning
confidence: 99%